ANALISIS TATA KELOLA KEUANGAN SMAIT BUAHATI ISLAMIC SCHOOL JAKARTA BERDASARKAN PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 48 TAHUN 2008 - Fiqiyah, Nur Mahda; Nurodin, Idang; Martaseli, ev (Jurnal Riset Akuntansi Politala, 2023)
This study aims to understand the process of preparing the School Budget Activity Plan (RKAS), budget realization, preparing financial reports at SMAIT Buahati Islamic School Jakarta, and understanding the financial governance of SMAIT Buahati Islamic School Jakarta. The research method used is qualitative with a descriptive approach. The data collection techniques used are interviews, observation, and documentation. The results showed that the planning process of school financial governance sourced from school fund finances and BOS funds begins with holding a limited meeting with the process of preparing RKAS and RAB, based on the plans needed by the school and the technical instructions for school BOS. The realization of financial governance at SMAIT Buahati Islamic School Jakarta, the principle of efficiency has not been followed properly. The preparation of financial reports is carried out routinely by making an Accountability Sheet (LPJ) for each activity that has been carried out.